2021
DOI: 10.1016/j.meegid.2021.104951
|View full text |Cite
|
Sign up to set email alerts
|

Designing an effective therapeutic siRNA to silence RdRp gene of SARS-CoV-2

Abstract: The devastating outbreak of COVID-19 has spread all over the world and has become a global health concern. There is no specific therapeutics to encounter the COVID-19. Small interfering RNA (siRNA)-based therapy is an efficient strategy to control human viral infections employing post-transcriptional gene silencing (PTGS) through neutralizing target complementary mRNA. RNA-dependent RNA polymerase (RdRp) encoded by the viral RdRp gene as a part of the replication-transcription complex ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 62 publications
3
30
0
Order By: Relevance
“…Several other in silico studies predicted siRNAs targeting ORF1ab [48][49][50][51], S gene [49,[51][52][53], ORF3 [49,51], E gene [49], M gene [49,51] and N gene [51,53] of SARS-CoV-2. Two in vitro studies further demonstrated a robust downregulation of S, M and N on the mRNA or protein levels by siRNAs in overexpression cell culture models [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Several other in silico studies predicted siRNAs targeting ORF1ab [48][49][50][51], S gene [49,[51][52][53], ORF3 [49,51], E gene [49], M gene [49,51] and N gene [51,53] of SARS-CoV-2. Two in vitro studies further demonstrated a robust downregulation of S, M and N on the mRNA or protein levels by siRNAs in overexpression cell culture models [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…The proper interaction between siRNA duplex and RISC complex, as well as guide siRNA strand and target mRNA inside RISC complex, are required to trigger a sufficient antiviral response via RNAi-mediated viral gene silencing[18]. Hence for interaction pattern analysis, molecular docking was carried over between siRNA (guide strand) and argonaute protein.…”
Section: Methodsmentioning
confidence: 99%
“…RNA interference or RNAi, the biological mechanism by which double-stranded RNA (dsRNA) induces gene silencing by targeting complementary mRNA for degradation (Figure 1)[18], is a huge breakthrough in disease therapy and is changing the way scientists analyse transcriptional activity[19] and it is a prospective tool for the control of human viral infections. Small interfering RNA (siRNA) is a double-stranded RNA of around 21 base pairs long RNA duplex bearing overhangs of two nucleotides on the 3′ end[20].…”
Section: Introductionmentioning
confidence: 99%
“…These siRNAs could combine SARS-CoV-2 mRNA targets, inducing greater inhibition of viral replication and reduced off-target effects ( Table 1 ) [ 91 ]. In addition, bioinformatics-based methods were also used to design siRNA targeting SARS-CoV-2 RdRp as a therapeutic agent [ 101 ]. Chen et al identified nine potential siRNA targets in the SARS-CoV-2 genome [ 102 ].…”
Section: Sirna Therapy—a Potential and Promising Antiviral Therapeuticmentioning
confidence: 99%